Effect of Bovine Serum Albumin Treatment on the Aging and Activity of Antibodies in Paper Diagnostics - Huang, Ziwei; Gengenbach, Thomas; Tian, Junfei; Shen, Wei; Garnier, Gil (Frontiers in Chemistry, 2018)
Paper and cellulosic films are used in many designs of low-cost diagnostics such as paper-based blood grouping devices. A major issue limiting their commercialization is the short stability of the functional biomolecules. To address this problem, the effect of relative humidity (RH) and bovine serum albumin (BSA) on the antibody bioactivity and the surface chemical composition of a paper blood typing biodiagnostic were studied. An IgM blood typing antibody was physisorbed from solution onto paper - with or without BSA pretreatment, and aged for periods up to 9 weeks at room temperature and under different RH conditions. The blood typing efficiency of the antibodies and the substrate surface chemical composition were analyzed by image analysis and X-ray photoelectron spectroscopy (XPS), respectively. This study tests two hypotheses. The first is that the hydroxyl groups in paper promote antibody denaturation on paper; the second hypothesis is that proteins such as BSA can partially block the hydroxyl groups with paper, thus preserving antibody bioactivity. Results show that high RH is detrimental to antibody longevity on paper, while BSA can block hydroxyl groups and prolong antibody longevity by almost an order of magnitude – regardless of humidity. This study opens up new engineering concepts to develop robust and marketable paper diagnostics. The simplest is to store paper and antibody based diagnostics in moisture proof packages.